Is digital mammography reducing radiation doses to women? (Brazilian Journal of Radiation Sciences, 2024)
This study aims to investigate the impact of national quality programs in mammography and technological advances in digital mammography units on the radiation doses delivered to women in Brazil. Radiation dose assessments in mammography units were conducted through a mail-based dosimetric system. For each unit of facilities that applied to one of the two national quality programs, a postal dosimetric system is dispatched, comprising an optically stimulated luminescent dosimeter (OSL) attached to the surface of a 4.0 cm thick polymethyl methacrylate (PMMA) phantom, simulating a compressed breast with 4.5 cm thickness. Testing instructions to expose the dosimetric phantom for assessing the mean glandular dose (MGD) are provided. Between 2012 and 2023, the programs evaluated the MGD in 1,687 mammography units of computed radiography (CR) and direct digital radiography (DR) technologies from 1,399 facilities located in all Brazilian regions. A total of 1,660 (70.5%) evaluations were carried out on CR technology mammography units and 696 (29.5%) on DR units, totaling 2,356 MGD evaluations. The overall average MGD was 1.60 ± 0.80 mGy, with 1.68 ± 0.83 mGy for CR technology and 1.42 ± 0.68 mGy for DR technology. A comparison of average MGD between the periods 2012 - 2018 and from 2019 onwards shows a dose reduction of 8.6% for CR systems and of 26.0% for DR systems (p = 0.000). As CR systems use analog mammography units, which did not undergo technological advances between the two periods, the reduction in doses observed is due to the actions of national quality certification programs and by using image plates for dual-sided reading or needle-based image plates. The reduction observed in DR systems is due to both national quality programs and technological advances in mammography units, especially the use of radiation beams generated by X-ray tubes with tungsten targets.
Keywords: mammography; mean glandular dose; national programs